Intellectual Capital, Capital Structure, Firm Size, Firm Age and Financial Performance - Esther Priscilla Rundjan; Merry Susanti (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to find out how the role of the components of intellectual capital and capital structure on financial performance in financial sector companies listed on the Indonesia Stock Exchange during 2018-2020. Samples were selected by purposive sampling method and valid data were 59 companies. The data processing technique uses multiple regression analysis assisted by the EViews 12 SV program and Microsoft Excel. The results of this study show that the three components of intellectual capital, namely structure capital efficiency, human capital efficiency and capital employed efficiency as well as capital structure have a significant influence on the company's financial performance. The implication of this study is that it is necessary to maintain the company's attention to employees, the values that can make the company unique, as well as company funding that will improve the company's financial performance that will provide a good signal for investors.